PMO-050 A survey of GP's knowledge and attitudes towards bariatric surgery in Scotland. (28th May 2012) - Kynaston, J; Mitchell, A; Bruce, D
Abstract : Introduction: 25% of Scotland's population are obese. The benefits of bariatric surgery are established however General Practitioners (GP's) influence equality of access to this treatment. This study examines GP's knowledge and attitudes to bariatric surgery in Scotland. Methods: An electronic questionnaire-based study was emailed to all 902 GP's within the NHS Highland, Grampian and Tayside health board regions in Scotland. The questionnaire was piloted with a convenience sample of GP's. Respondents were asked their age, sex and eight questions examining their knowledge, experience and opinions regarding bariatric surgery. Results: 230 GP's completed the survey (25.4% response), a further 11 incomplete submissions were not analysed. 60% (n=139) of respondents were female. 93% of GPs acknowledge they often encounter weight management issues. 62% (n=142) of GPs acknowledge bariatric surgery has an important role in weight management and 69% (n=159) acknowledge it's importance in the management of the obesity related co-morbidities. 30% (n=68) of GPs are not aware of NICE/SIGN guidelines and 57% (n=132) are not aware of their local referral criteria. 40% (n=103) of GPs have never referred. Of those that have, 34% (n=43) of referrals were to the private sector. 76% (n=174) of GPs are not comfortable managing patients who have undergone bariatric surgery. 8% (n=17) of GPs believe the primary role of bariatric surgery is cosmetic. Of these, 47% (n=9) are aged 25–40 years. Conclusion: Weight management issues are common in primary care and most GP's support bariatric surgery. However a third of GP's are unaware of national guidelines and half do not know how to refer to their local service in Northern Scotland. Most GP's are not comfortable providing long-term care after bariatric surgery. These findings suggest GP's require education and support to allow their patients access to bariatric surgery. Competing interests: None declared.